(untitled) (World Bulletin of Social Sciences, 2023)
This research aims to study market orientation in the banks of Diwaniyah Governorate in Iraq and its impact on achieving a competitive advantage compared to competitors working in the banking sector in the same region. The research used questionnaires to collect data on the distributed variables. 130 questionnaires for employees in banks, (118) questionnaires were returned, (110) valid forms for analyzing research procedures, the researcher used (SPSS V20.0) to find a relationship between the variables, and the study revealed significant relationships between closely related market orientation. With a competitive advantage, The study reached a set of conclusions and recommendations to improve the position of banks in environmental competitiveness to reach banks with outstanding performance. This study extracted the concept of market orientation to find out how these methods help in improving the competitive advantage of banks in the Diwaniyah Governorate